Scientific and Technological Advances as Current Challenges to the Biological Weapons Non-Proliferation Regime - D. L. Poklonskii (Вестник войск РХБ защиты, 2024)
The recent advances in biological sciences and biotechnology have resulted in new knowledge and capabilities that  challenge existing understandings of biological threats and biological weapons (BW). The purpose of the article is to  evaluate scientific and engineering decisions that pose potential challenges to the biological weapons non-proliferation  regime and can reduce barriers to their development, production and use. Materials and methods. The scientific articles  available through the PubMed, Google Scholar and Russian Electronic Library databases were used in the research.  The method of analysis is the description. The results of the research. The success of biotechnology provides impetus for  experimentation with biological weapons, particularly by non-state actors such as terrorist organizations and extremist  groups. Transformative changes are occurring in areas not directly related to microbiology. However, the potential for  their malicious use is no less of a concern than the development, production and stockpiling of biological weapons.  The transformation of the concept of «biological threat» is traced. It becomes more complex and includes elements  from other fields outside of biotechnology and the traditional understanding of biological weapons. In addition to  biotechnology and synthetic biology, such technologies that are directly related to the BTWC issue, may include:  additive manufacturing based on 3D printing technologies; big data analysis and artificial intelligence technologies;  nanotechnology and materials science, as well as biological research automation and robotics. Conclusion. Many dual-use technologies have received close attention from the scientific community and international experts, but this does  not always contribute to an accurate and balanced understanding of their potential in the context of BTWC issues. The  convergence of new and emerging disciplines is creating new areas of scientific knowledge that address the problem of  non-proliferation of biological weapons, which requires the expert community to make a balanced assessment from  the point of view of both dual use and the risk of excessive prohibition and negative impact on further scientific and  technological progress.